Error Reporting among Nurses Working at Yasuj Shahid Beheshti Hospital in 2014 - E Nouhi; A Dehbanizadeh; M Zoladl; KH Saeedi; A Paghan (Iran University of Medical Sciences, 2016)
Abstract Background & Aims: Nursing report is one of the important documents in a patients' record and it is also the best tool which can help to evaluate the nurses' activities in 24-hour periods. Therefore, committing error in report writing may have consequences for a nurse. This study aims to determine the status of error reporting among nurses. Materials & Methods: This study is a descriptive-analytic one and the participants were all the nurses (161 Nurse) working at Yasuj Shahid Beheshti hospital of Yasuj, Iran in 2014. The data collecting tool was a researcher-made questionnaire that contains 19 questions about the demographic characteristics of nurses and the reporting error among them. The data was analyzed using descriptive statistics, coefficient of dispersion, t-test and ANOVA and SPSS software version 16. Results: Based on the findings of study, only 85/71% of the nurses have committed reporting error and writing long reports was the most frequent error (247 cases, 21%). The mean of error reporting for each nurse was 1/22 in a one-month period. There were significant relationships among reporting errors and the sex and work experiences of the nurses. Conclusion: The results showed that nursing reports have a poor quality. It seems that creating legal and cultural infrastructures for error reporting, developing the training programs and continuous monitoring are necessary to improve the quality of nursing reports.